Implementation Of Civil Case Settlement Before And After The Enactment Of E-Court System In Electronic And Conventional Courts - Rahmawati Putri Musa; Fence M. Wantu; Mohamad Taufiq Zulfikar Sarson (Lembaga Pengembangan Kinerja Dosen, 2024)
This research explain how to implement civil cases settlement before and after the implementation from of E-Court system in electronic and conventional court. on this case it explains that civil cases settlement in a modern manner is described according to Supreme Court Regulation Number 7 of 2022 while conventionally described according to HIR / RBG. Before the advent of system E-Court, the testing method was conducted conventionally. The optimization of these two forms of civil case settlement is then examined according to Law Number 48 of 2009 concerning Judicial Power where the judiciary is administered out with the principles of simple, fast and low cost. This research is a normative legal research with Statute Approach and Conceptual Approach methods. The research concluded: first, the existence of court dualism is still needed for justice seekers who still need conventional lawyers. Second. The implementation of Civil Case Settlement with the presence of E-Court as an effort to realize the principles of simple, fast and low cost in reality has not been optimal, however, E-Court has not fully resolved the cases received by the Supreme Court and the lower courts. That is, most cases are still conducted conventionally.